PKM Pelatihan Kader Pimpinan Wilayah Nasyiatul ‘Aisyiyah Sumatera Utara Menuju Terwujudnya Kader Nasyiah Berkemajuan di Era Milenial - Mavianti Mavianti; Rizka Harfiani (IHSAN : JURNAL PENGABDIAN MASYARAKAT, 2019)
Cadre training is needed to form a militant cadre who will continue the continuity of the women's organization, Nasyiatul isy Aisyiyah. Nasyiah who has a role as the successor, pioneer and executor ‘Aisyiyah in the future. PKM Cadre Training of Nasyiatul 'Aisyiyah North Sumatra Regional Leaders Towards the Realization of Nasyiat Cadres Joining in the Millennium Era was carried out due to the uniformity of leadership in Nasyiatul' Aisyiyah, the orderly needs of leadership cadres, the need to manage training in the region, and the need for corps Nasyiatul 'Aisyiyah instructor and cadre map in Nasyiatul' Aisyiyah. The method used in this PKM is conducting cadre training activities (DANA III) in collaboration with the Nasyiatul Regional Leader isy Aisyiyah Sumatera Utara, specifically the Cadre Department. The participants were provided with quality materials that could be applied in their respective regions. At the end of the program it is expected that the participants are expected to become a cadre of sustainability at the regional level to be able to continue regaining the regional level so that there will be an increasing number of Nasyiah cadres who are indeed militant.